Preliminary estimates of project turnover in the Tondo foreshore Dagat-Dagatan development project - Reforma, Mila A. (1981)
The determination of the rate of turnover of residents in Tondo is informative as the degree to which the project has contributed to the stability of the population can be taken as an indicator of the success of the project. The study looks into the population structure to assess the possible changes that have accompanied the project since upgrading began and the extent to which the project has been able to further the objectives of population stabilization. The characteristics of households that left, that of households that stayed, and new households coming into the area were analyzed to determine the manner in which the Project has caused the dislocation of households in the project area and how turnover has affected the structure of the population in the project area.
Keywords: Human settlements; Informal settlements; Squatter settlements -- Statistical methods